2022
DOI: 10.1002/mnfr.202200167
|View full text |Cite
|
Sign up to set email alerts
|

Spicy Food and Chili Peppers and Multiple Health Outcomes: Umbrella Review

Abstract: Spicy foods and chili peppers contain the primary ingredient capsaicin, which has potential health benefits. However, their efficacy in some health outcomes is also fiercely disputed, and some side effects have been confirmed. To assess the quality and strength of the associations between spicy food and chili pepper consumption and different health outcomes. An umbrella review is performed in humans. Eleven systematic reviews and meta‐analyses with a total of 27 findings are identified. The health effect of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…However, no significant difference in total cholesterol (202 mg/dL versus 205 mg/dL) or HDL-cholesterol (50 mg/dL versus 51 mg/dL) levels were detected between chili-eaters and non-eaters, respectively. In accordance, a recent umbrella review of 11 systematic reviews and meta-analyses found no significant association between spicy food intake and blood glucose, plasma insulin, and hemoglobin A1 c levels [ 56 ].…”
Section: Eating Chili Pepper Makes You Healthy?mentioning
confidence: 93%
“…However, no significant difference in total cholesterol (202 mg/dL versus 205 mg/dL) or HDL-cholesterol (50 mg/dL versus 51 mg/dL) levels were detected between chili-eaters and non-eaters, respectively. In accordance, a recent umbrella review of 11 systematic reviews and meta-analyses found no significant association between spicy food intake and blood glucose, plasma insulin, and hemoglobin A1 c levels [ 56 ].…”
Section: Eating Chili Pepper Makes You Healthy?mentioning
confidence: 93%
“…The study found that this co-administration resulted in elevated levels of insulin-like growth factor 1 in the serum, leading to a notable decrease in systolic and diastolic blood pressure. Within the realm of scholarly investigations, a study by (Ao et al, 2022) revealed that fermented red chili pepper supplementation may play a vital role in improving systolic blood pressure (SBP) and diastolic blood pressure (DBP). However, there was no significant association between the consumption of red chili pepper and systolic blood pressure, diastolic blood pressure, and heart rate.…”
Section: Global Perspective Of Chili Pepper As a Functional Foodmentioning
confidence: 99%
“…It has been suggested that the regular consumption of chili peppers may have potential benefits in preventing and managing chronic conditions such as arthritis, diabetes, obesity (Huei et al, 2020), hypertension (Ao et al, 2022), and cardiovascular diseases (Bonaccio et al, 2019).…”
Section: Relevance To Lesothomentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the same year, Szallasi et al [66], analyzing clinical studies carried out with capsiate, did not observe a significant influence of non-pungent capsinoids on body weight and obesity. Some reviews and clinical studies carried out with red [71,84,106] or black pepper [107,108] have observed beneficial effects on human health. Since capsaicin and chili peppers are the main components that give spicy characteristics to foods, it could be expected to associate the increase in spicy food consumption with the increase in capsaicin's beneficial effects.…”
Section: Effect Of Non-pungent Capsinoids and Spice Foodsmentioning
confidence: 99%